Independence in Activities of Daily Living (ADL) Among People with Visual Impairments at Sentra Wyata Guna Bandung - Indriya, Alifia Putri; Aritonang, Admiral Nelson; Hekmatyar, Versanudin (Indonesian Journal of Social Work, 2026)
Independence in Activities of Daily Living (ADL) constitutes a fundamental aspect of the lives of people with visual impairments, enabling them to live with autonomy rather than complete reliance on others. This study provides an empirical account of the independence of persons with visual impairments at Sentra Wyata Guna Bandung, analyzed across four dimensions: (1) responsibility, (2) autonomy, (3) initiative, and (4) self-control. Employing a descriptive qualitative design, participants were selected through purposive sampling, and data were collected using in-depth interviews, observation, and document review. The findings reveal that, in terms of responsibility, participants exhibited compliance with schedules and institutional regulations, demonstrated through consistent engagement in self-care and vocational training. Autonomy was reflected in their confidence to manage daily tasks independently and in their freedom to select training programs aligned with personal interests, thereby shaping orientation toward independent living after leaving the center. Initiative emerged in the proactive use of adaptive strategies in ADL and the independent utilization of assistive devices such as folding canes, talking watches, and braille slates. Nevertheless, challenges persisted in the domain of self-control, particularly with regard to vulnerability to emotional influences, partial limitations in ADL performance, and continued reliance on external support. In response, this study introduces a program to enhance the self-control of people with visual impairments in performing Activities of Daily Living (ADL) at Sentra Wyata Guna Bandung. The program seeks to reinforce the role of social workers as facilitators through three key strategies: (a) the development of training modules, (b) technical training in emotional regulation, ADL, and Orientation & Mobility (O&M), and (c) modification of assistive devices to foster greater independence.